The Algorithmic Canvas: On the Autopoietic Redefinition of STP in the Age of Strategic Resilience - Simon Suwanzy Dzreke; Semefa Elikplim Dzreke (Sultan Publisher, 2026)
Traditional Segmentation, Targeting, and Positioning (STP) frameworks demonstrate significant deficiencies in unstable markets, with actual data revealing a 67% decline after six months. This research redefines STP not as a structured process but as an autopoietic system—an entity that self-organizes and constantly redefines its limits. It presents the Algorithmic Canvas as the operational medium that facilitates this paradigm, in which segmentation, targeting, and positioning parameters dynamically evolve through human-AI collaboration. Using a sequential mixed-methods design that included a 6-month Fortune 500 lab ethnography (n=23), a computational analysis of 150 million customer interactions, and an empirically based agent-based simulation (ABS), the study shows that autopoietic STP implemented through the Canvas is 44% more resilient (p < 0.01) to market shocks and cuts strategic planning cycles by 90% compared to traditional models. Algorithmic co-creation methods enhanced the identification of substantial market fluctuations by a factor of 5.8. The study enhances the Autopoietic STP Framework and empirically substantiates Canvas Design Principles, effectively addressing algorithmic myopia and offering businesses a framework for improved adaptability and resource efficiency during turbulent conditions.